Seeing diplomatic constellations through diplomatic relations: an analysis of the positioning of Zimbabwe and the UK in Zimbabwean news articles - Mvundura, Emaculate Musimeki (Rhodes University, Faculty of Humanities, Department of Linguistics and Applied Language Studies)
This study examines the positioning of Zimbabwe and the United Kingdom (UK) in the language of news articles about diplomatic relations between the two countries published in two prominent Zimbabwean newspapers, The Herald and The Standard, between 2016 and 2020, using Systemic Functional Linguistics (SFL) and Legitimation Code Theory (LCT). Zimbabwe's present diplomatic discourses are a product of its colonial and post-independence history. This thesis places The Herald and The Standard within the larger context of the Zimbabwean media landscape as a state-owned and a privately owned newspaper, respectively. It contends that the two newspapers influence the positioning of Zimbabwe and the United Kingdom in public spheres where readers engage with the news concerning diplomatic ties. The research begins with a corpus-based examination of 42 news articles published between 2016 and 2020 in The Herald and The Standard. The investigation identified several angles through which Zimbabwe and the UK are positioned in the coverage. Zimbabwe is positioned through reference to its reform agenda, intentions for free and fair elections, and its diplomatic re-engagement drive. The UK is positioned as a source of development funding and new trade agreements, while improved diplomatic relations and the removal of restrictive measures against Zimbabwe are anticipated. Fine-grained analysis was conducted on four articles, two from each newspaper, selected to reflect the trends found in the corpus analysis. The fine-grained analyses showed how linguistic resources contributed to the positioning of the UK and Zimbabwe. Complementary analyses of these articles were conducted using LCT and SFL to describe how readers' knowledge of diplomatic relations is built using language in The Herald and The Standard. The study used the concepts of constellations and cosmologies from LCT to demonstrate how diplomatic knowledge is built in these news articles. In the articles, the constellations are related to policies such as Zimbabwe's reform agenda, people (diplomats and government officials) and moral judgments. Both newspapers contain both positive and negative positioning of Zimbabwe and the UK. However, The Standard is generally critical of removing the UK's sanctions on Zimbabwe and of the Zimbabwean government's reform agenda. Meanwhile, The Herald justifies Zimbabwe's Fast-track Land Reform Programme as resulting from Britain's refusal to fund a land redistribution programme as per the 1979 Lancaster House Agreement. The use of SFL's Appraisal framework helps to examine the linguistic resources used by The Herald and The Standard to describe the positioning of the two countries in relation to each other. Lexical strings help to establish diplomatic positioning in the news articles. These couple with Appraisal to accomplish individuation and affiliation. Affect and Judgement resources revealed the decisions taken by the UK to solve the conflict by encouraging the implementation of a reform agenda by Zimbabwe. Negative evaluation is consistently used to disalign with sanctions. The emerging patterns in the data show that diplomats representing the UK affiliate with Zimbabwe's stated economic and political reforms, and the government of Zimbabwe affiliates with the new trade agreement between Zimbabwe and the UK. At the same time, the UK diplomats individuate away from human rights abuses and the Fast-track Land Reform Programme. Affiliation strengthens confidence in diplomatic ties between Zimbabwe and the UK because the emphasis is placed on restoring them despite the conditions attached. The Herald and The Standard position Zimbabwe as a reformed country ready to implement policies to improve citizens' lives and as a country violating human rights and the rule of law. They position the UK as asserting power over Zimbabwe, willing to resolve the crisis through its foreign policy, and credited for assisting Zimbabwe. This strengthens re-engagement in diplomatic relations and commercial trade between the UK and Zimbabwe. In light of these findings, Zimbabweans are encouraged to cultivate an awareness that enables them to reflect on the challenges associated with diplomatic discourses and the implications for critically analysing the re-engagement initiative. They can promote re-engagement by being cognisant of specific values portrayed in The Herald and The Standard and challenging these values in the light of policy transformation to revive the relations between the two countries. The re-engagement process requires a transformation in Zimbabwe's modus operandi to improve the country's positioning in the diplomatic relations between it and the UK.
Keywords: Systemic functional linguistics; Linguistic analysis (Linguistics); Journalism Language; Political media; Journalism -- Political aspects -- Zimbabwe; Great Britain -- Foreign relations -- Zimbabwe; Diplomacy Language